2016
DOI: 10.1007/s00276-016-1776-9
|View full text |Cite
|
Sign up to set email alerts
|

An update on the variations of the orbital blood supply and hemodynamic

Abstract: PurposeSeveral variations of the arterial blood supply of the orbit have been reported over the years. This review is aimed to provide an update focusing on three important issues: (a) variations of the ophthalmic artery origin; (b) contribution of the external carotid artery to the orbital blood supply; (c) orbital hemodynamic.MethodsA PubMed and Google search was carried out with the following keywords: ophthalmic artery origin, ophthalmic artery anastomoses and ophthalmic artery anatomy.ResultsThe site of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 57 publications
0
45
1
Order By: Relevance
“…This difference may be due to poor sensitivity of TOF MRA for detecting OA variants. Compared to the results found in cadaveric studies, other angiographic studies have also reported lower OA variant prevalence rates [5,8,9].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This difference may be due to poor sensitivity of TOF MRA for detecting OA variants. Compared to the results found in cadaveric studies, other angiographic studies have also reported lower OA variant prevalence rates [5,8,9].…”
Section: Discussioncontrasting
confidence: 58%
“…This parameter was first applied to ascertain the efficacy of angiography for visualizing orbital arteries by Bracco et al [7]. This novel numerical index is the ratio of the frequency of angiographic visualization of Ophthalmic Res 2020;63:341-346 DOI: 10.1159/000502980 an arterial structure and its true incidence [8]. Previously published dissection-based studies are accepted as true anatomic incidence in this field.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recent reports, however, disprove this interpretation and consider both PrDOA and PrVOA to be intradural branches of ICA that enters the orbit through the optic canal and related the cavernous origin of the OA to the deep recurrent OA, a branch of the ILT. [5][6][7]11,14 A key finding in the presented case is the segmental hypoplasia of the ICA between the origins of ILT and OA. Lasjaunias and Santoyo-Vazquez divided the ICA into six independent segments, each corresponding to the origin of a specific embryonic artery.…”
Section: Discussionmentioning
confidence: 70%
“…The rationale for the medial canthus technique is its safety. In both sagittal and coronal axes, this approach could represent the safest site, with few main adjacent structures (nerves, vessels, or muscles) [6,7]. Additionally, the preferred location of staphyloma is to be temporal and not nasal [8].…”
Section: Introductionmentioning
confidence: 99%